Rapidly Progressive Pulmonary Fibrosis in a Patient Treated with Danazol for Idiopathic Thrombocytopenic Purpura - Smita Pakhale; Yuri Moltyaner; Dean Chamberlain; Neil Lazar (Canadian Respiratory Journal)
The case of a patient that developed pulmonary fibrosis two months after initiation of danazol for treatment of idiopathic thrombocytopenic purpura is described. Bilateral pneumothoraxes and pneumomediastinum complicated the rapidly fatal pulmonary fibrosis. An association between danazol therapy and the development of pulmonary fibrosis is suspected. There is only one other case report with this connection in the literature.